A2.17 Synoviocytes Change Phenotype and Function after Treg-Depletion in Arthritic Mice. (25th February 2013) - Böttcher, M; Irmler, I; Wunrau, C; Korb-Pap, A; Schett, G; Pap, T; Kamradt, T
Abstract : Purpose/Objective: Immunizstion with Glucose-6-phosphate isomerase (G6PI) induces arthritis in susceptible strains of mice. Depletion of regulatory T cells (Tregs) prior to immunisation switches the usually acute, self-limiting course to a non-remitting, destructive arthritis. This provides a possibility to study molecular switches for the transition from acute, self-limiting to chronic, destructive arthritis within one mouse model. To examine the role of fibroblast-like synoviocytes (FLS), which are known to modulate immune responses via the production of pro- and anti-inflammatory mediators, the phenotype and function of FLS from mice with either acute, self-limiting or non-remitting, destructive arthritis was studied. Materials and Methods: FLS from DBA/1 mice that developed either the acute or the chronic form of arthritis were isolated from joints over a time course of 56 days. To investigate the phenotype of FLS ELISA studies as well as zymography have been performed. For the functional clarification of those cells the matrix-associated transepithelial resistance invasion (MATRIN) assay and a cartilage attachment assay have been used. Furthermore, FLS have been transferred in vivo into the knee joints of immunodeficient mice and the joints have been scored histologically. Results: FLS from Treg-depleted mice produced significantly more cytokines (e.g. Interleukin 6 (IL-6)) upon stimulation with other cytokines, growth factors and TLR ligands. This increased susceptibility to cytokine stimulation in chronic animals compared to acute ones is observable throughout the disease course (56 days). Furthermore, the secretion and activity of matrix metalloproteases (MMPs) was enhanced in the FLS from chronic mice compared to samples from acute ones. Additional functional differences include the collagen-destructive potential and the potential to attach and eventually invade wild type cartilage. Here, FLS from Treg-depleted chronic arthritic mice showed a higher invasive and destructive potential. Ultimately, FLS from Treg-depleted mice were able to destroy cartilage in immunodeficient mice. Conclusions: Our results are compatible with the hypothesis that uninhibited inflammation in the early phase of Treg-depleted mice causes the acquisition of an autonomously aggressive phenotype of synoviocytes which contribute to the switch from acute to chronic arthritis even in the absence of late support from T and B lymphocytes.